Orientation of Gp96 and Calreticulin T-cell epitopes in a multiepitope HPV16 E7 vaccine construct affects predicted immunostimulatory properties: An in silico and expression validation study - Giti Esmail Nia; Zahra Shahosseini; Elahe Akbari; Hadi Bamehr; Fatemeh Heidarnejad; Monireh Mohsenzadegan; Azam Bolhassani; Mohammadmorad Farajollahi (PLoS ONE, 2026)
Heat shock proteins (HSPs) can be used as adjuvants to develop therapeutic vaccines, as they enhance the cross-presentation of related tumor antigens and stimulate T cells. In this study, the immunostimulatory properties of gp96 and calreticulin was evaluated to enhance HPV16 E7-based vaccines effectiveness. In silico evaluation was performed to select epitopes from HSPs based on high binding affinity to MHC-I/II, strong immunogenicity, and population coverage. Six novel multiepitope constructs harboring conserved epitopes of E7, gp96, and calreticulin were designed in different orientations. Molecular docking was performed between these constructs and signaling (TLRs) and endocytic (CD14, CD91, LOX-1, and SREC-1) receptors. After determination of an effective construct in molecular docking and MD simulation, prokaryotic expression plasmid containing eight (CTL/HTL) epitopes from HPV16 E7, gp96, and calreticulin in suitable orientation was prepared, and the recombinant multiepitope peptide was generated in E. coli system. Our data showed that the gp96-CRT-E7 construct had superior docking scores with receptors (especially TLR2 and LOX-1), suggesting stronger stimulation of both innate and adaptive immunity than other constructs. It was predicted to be non-toxic, non-allergenic, antigenic, immunogenic, and structurally stable. Moreover, the multiepitope gp96-CRT-E7 fusion peptide was expressed in the Rosetta strain under conditions of OD 600 : 0.6–0.7, 0.5 mM IPTG, temperature of 18ºC, and 24 hours after IPTG induction, and purified through affinity chromatography under native conditions. Generally, successful results of in silico and expression validation of the multiepitope gp96-CRT-E7 fusion peptide showed its strong potential as a novel candidate for HPV16 vaccine development.